Accuracy of 3D printed models and implant-analog positions according to the implant-analog–holder offset, inner structure, and printing layer thickness: an in-vitro study. (October 2022) - Jin, Gan; Shin, Seung-Ho; Shim, June-Sung; Lee, Keun-Woo; Kim, Jong-Eun
Abstract: Purpose: This study aimed to determine how the implant-analog–holder (IAH) offset, inner structure, and printing layer thickness influence the overall accuracy and local implant-analog positional changes of 3D printed dental models. Methods: Specimens in 12 experimental groups (8 specimens per group) with different IAH offsets, inner structures, and printing layer thicknesses were printed in three dimensions using an LCD printer (Phrozen Shuffle) and digitized by a laboratory scanner (Identica T500). The trueness and precision of the printed model as well as the angular distortion, depth deviation, and linear distortion of the implant analog were evaluated using three-way ANOVA. Results: The positional accuracy was significantly higher for IAH offsets of 0.04 mm and 0.06 mm than for one of 0.08 mm, for a hollow than a solid inner structure, and for a printing layer thickness of 100 µm than for one of 50 µm (all P <.001). Conclusions: The accuracies of the 3D printed models and the implant-analog positions were significantly affected by the IAH offset, inner structure, and printing layer thickness. Clinical significance: Given the observation of this study, premeditating the IAH offset of 0.06 mm, hollow inner structure, and printing layer thickness of 100 µm before printing can help clinicians reach the optimum overall printing accuracy and minimum the local positional changes of the implant-analogs.